ADVANCE TECHNOLOGIES IN BUSINESS MANAGEMENT: A CASE OF UZBEKISTAN (World Bulletin of Public Health, 2025)
This article investigates the incorporation and assimilation of cutting-edge technologies in business management within Uzbekistan as of 2024. It emphasizes significant technological innovations, including artificial intelligence (AI), blockchain, financial technology (fintech), data analytics, and cloud computing, which are transforming the business environment in Uzbekistan. The study analyzes the underlying factors propelling this technological evolution, such as governmental policies, the enhancement of digital infrastructure, and the rise of innovation in the private sector. The article also examines the obstacles encountered by enterprises in Uzbekistan, including disparities in digital proficiency, infrastructural constraints, and regulatory intricacies. Furthermore, the outlook for these technologies and their potential influence on the economy, particularly in domains such as e-commerce, finance, and manufacturing, is explored. The article ultimately concludes that, despite the prevailing challenges, Uzbekistan is well-equipped to emerge as a regional leader in business technology through sustained investment in digital advancement
Keywords: Uzbekistan; business management; artificial intelligence